Fluorescence Imaging of Fast Retrograde Axonal Transport in Living Animals - Dawid Schellingerhout; Lucia G. Le Roux; Sebastian Bredow; Juri G. Gelovani (Molecular Imaging, 2009)
Our purpose was to enable an in vivo imaging technology that can assess the anatomy and function of peripheral nerve tissue (neurography). To do this, we designed and tested a fluorescently labeled molecular probe based on the nontoxic C fragment of tetanus toxin (TTc). TTc was purified, labeled, and subjected to immunoassays and cell uptake assays. The compound was then injected into C57BL/6 mice ( N = 60) for in vivo imaging and histologic studies. Image analysis and immunohistochemistry were performed. We found that TTc could be labeled with fluorescent moieties without loss of immunoreactivity or biologic potency in cell uptake assays. In vivo fluorescent imaging experiments demonstrated uptake and retrograde transport of the compound along the course of the sciatic nerve and in the spinal cord. Ex vivo imaging and immunohistochemical studies confirmed the presence of TTc in the sciatic nerve and spinal cord, whereas control animals injected with human serum albumin did not exhibit these features. We have demonstrated neurography with a fluorescently labeled molecular imaging contrast agent based on the TTc.